The Influence of Top Management Support, HR Technology Infrastructure, and System Reliability on Digital HRM Effectiveness in Financial Technology Companies - Haris Karyadi; Dasep Supriatna; Tyahya Whisnu Hendratni; Pipit Sundari; Putri Wahyu Novika; Ricky Rizkie (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The expansion of financial technology needs companies to adopt digital human resource management systems which enhance their operational processes to maintain their competitive edge in the market. The study investigates the impact of executive leadership backing and human resource technology systems together with system reliability on the effectiveness of digital human resource management in financial technology organizations. The research uses a quantitative research design to test its hypotheses through an explanatory research approach. The researchers conducted a survey using a structured questionnaire which they distributed to 150 employees from Indonesian fintech companies who were selected through purposive sampling. The researchers conducted validity testing and reliability testing plus classical assumption testing before they performed multiple linear regression analysis for data analysis. The research shows that digital HRM effectiveness needs top management support together with HR technology systems and system reliability because these factors influence system performance of the system. The study shows that digital HRM effectiveness requires both technological components plus organizational support and system dependability. The study demonstrates how human resource management and information systems research benefit from understanding how managerial elements and technical components work together to develop digital HRM systems. The study findings provide financial technology companies with recommendations for developing HR management solutions which achieve reliability and long-term effectiveness through digital methods.